(untitled) (Scientific journal of the Fergana State University, 2023)
The article discusses the histori cal philosophical essence of the concept of good-neighbour relations. Also, the role of historical memory as a necessary factor in the formation of the worldview of the individual is considered, and at the same time the awareness of the influence of this factor on the impact of the socio-political process of the entire region is taken into account